2011
DOI: 10.1111/j.1757-1707.2011.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Reed canary grass cultivation mitigates greenhouse gas emissions from abandoned peat extraction areas

Abstract: We studied the impact of reed canary grass (RCG) cultivation on greenhouse gas emission in the following sites of an abandoned peat extraction area in Estonia: a bare soil (BS) site, a nonfertilized Phalaris (nfP) plot, a fertilized Phalaris (fP) plot, and a natural bog (NB) and a fen meadow (FM) as reference areas. The C balance and global warming potential (GWP) were estimated by measuring CO 2 , CH 4 , and N 2 O emissions and aboveground and belowground biomass variations. The high CO 2 flux from the nfP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 47 publications
4
38
1
2
Order By: Relevance
“…On an annual basis, the average TER (+1000 g C m −2 ) for our study was within the range of what has been reported earlier for RCG cultivations at the comparison site (+480 g C m −2 , Shurpali et al, 2009), in cut-away peatland Estonia (+600 g C m −2 , 2-year study, Mander et al, 2012) and in the organic agricultural field in Denmark (+1900 g C m −2 , Kandel et al, 2013a). When compared to annual TER values for switchgrass, hybrid poplar and Scots pine forest (Skinner and Adler, 2010;Jassal et al, 2013;Kolari et al, 2009), the annual TER of the present study is higher.…”
Section: Discussionsupporting
confidence: 89%
“…On an annual basis, the average TER (+1000 g C m −2 ) for our study was within the range of what has been reported earlier for RCG cultivations at the comparison site (+480 g C m −2 , Shurpali et al, 2009), in cut-away peatland Estonia (+600 g C m −2 , 2-year study, Mander et al, 2012) and in the organic agricultural field in Denmark (+1900 g C m −2 , Kandel et al, 2013a). When compared to annual TER values for switchgrass, hybrid poplar and Scots pine forest (Skinner and Adler, 2010;Jassal et al, 2013;Kolari et al, 2009), the annual TER of the present study is higher.…”
Section: Discussionsupporting
confidence: 89%
“…Shurpali et al, 2008;Mander et al, 2012;Salm et al, 2012). While the addition of WT or VMC improved the performance of the R eco models at some of the sites, the improvement was only slight and this is likely due to the fairly narrow range of WT and VMC values recorded over the course of the 12-month study (e.g.…”
Section: Effects Of Drainage Levelmentioning
confidence: 99%
“…Järveoja et al, 2012;Mander et al, 2012;Salm et al, 2012;Strack et al, 2014), (c) no data from ROI or UK peatlands were included in the IPCC derivation, which might mean that the Tier 1 value may not be appropriate for these countries, and (d) no distinction is made between industrial or domestic extraction sites, despite large differences in their drainage, vegetation cover and management characteristics. In addition, previous studies of peatland fire EFs have focused on the boreal peatlands of Alaska (Yokelson et al, 1997) and Canada (Stockwell et al, 2014) and the temperate peatlands of Minnesota (Yokelson et al, 1997) and North Carolina (Stockwell et al, 2014).…”
Section: Wilson Et Al: Derivation Of Greenhouse Gas Emission Factmentioning
confidence: 99%
See 1 more Smart Citation
“…Pangala et al (2010) studied the impact of gypsum (CaSO 4 Á2H 2 O) and ochre on the CH 4 emission from a FWS CW treating farm wastewater in Scotland and found that the application of 10 tons of gypsum ha À1 to the sediment core reduced CH 4 emissions by 28%, whereas the addition of 5 tons of ochre ha À1 caused methane emission to decrease by 63% (Pangala et al, 2010). Similarly, Mander et al (2012) found a significant negative correlation between the CH 4 flux and the sulfate concentration in peat, and on SO 4 2À and Ca 2+ concentrations in soil water .…”
Section: Effect Of Different Filter Materials On Greenhouse Gas Emissmentioning
confidence: 97%